Coaches` learning and sustainability in high performance sport - Rynne, S. B.; Mallett, C. J. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
In undertaking their complicated and multi-faceted work, high performance coaches have previously been shown to be influential in the performance of athletes. It has also been noted that high performance coaches are learners by necessity. However, what remains unclear is how coaches` learning influences their engagement in sustainable practice. This study draws on three cohorts of full-time high performance coaches employed in Olympic and professional sports throughout Australia. Semi-structured interviews were conducted face-to-face and were inductively analysed. The results revealed that the coaches were presented with a variety of opportunities to learn, with the most valued sources being `learning on the job`, `discussions with others` and `experience as athletes`. These unmediated learning opportunities are critiqued along with other mediated opportunities in relation to notions of sustainability. The dominance of unmediated sources of learning meant that sustainable practice was present but was not assured. Sustainable practice is also discussed in relation to the dominant models of high performance athlete development and the demands of coaching work.